Analytical hierarchy process for assessing sustainability: Indicators of public transportation systems, pedestrians and feeder services in developing countries. Issue 4 (5th October 2015) - Kumar, Ravindra; Madhu, Errampalli; Dahiya, Amit; Sinha, Sanjeev
Abstract : Purpose: – The purpose of this paper is to study the analytical hierarchy process (AHP) based on assessment of sustainability indicators for public transportation system including pedestrians and feeder services in developing country. Design/methodology/approach: – A hybrid approach based on the AHP is considered for assessment of the sustainability of public transportation system including pedestrians and feeder services. Sustainability related indicators for public transportation system (namely for metro, bus and feeder bus) and pedestrians based on past data were reviewed and subsequently, more important indicators catering needs of developing country have been added to achieve significant sustainability score and a total of 17 indicators were selected for assessment of comprehensive sustainability (seven indicators under economic, six under social and four under environmental categories). Findings: – For quantifying the assessment, specific user interview surveys are performed in south Delhi region and accordingly perception of user and transportation-related operational characteristics of the public transport system were also collected. Preliminary result shows air pollution in environmental category, public health in social category and productivity in economic category is most influential parameters in developing country. Originality/value: – AHP method is applied for rating the criteria and setting out the priority of designed sustainable indicators. Subsequently sustainable mitigation measures and scenarios for the study area can be evaluated utilizing developed comprehensive sustainability indicator for public transportation system including pedestrian and feeder services available in developing country.